Hubungan Tingkat Pengetahuan Dan Sikap Dukun Beranak Terhadap Tindakan Pertolongan Persalinan - Yulia Irvani Dewi; Desnen Salti (Fakultas Keperawatan, Universitas Riau, 2012)
The purpose of this study is to determine the correlation between knowledge and attitude toward the actions traditional birthAttendants childbirth aid. The research method is descriptive correlation with cross sectional approach. The study was conductedin District XIII Koto Kampar, Kampar regency with the number of samples taken 30 people in total sampling with respect to theinclusion criteria. Method analysis data used is the univariate analysis with frequency distribution and bivariate analysis usingChi Square. The results showed correlation between Traditional Birth Attendants knowledge of childbirth aid measures with p= 0.046 < = 0.05 and there is a relationship Traditional Birth Attendants attitudes toward childbirth aid measures with p =0.008 < = 0.05. Based on the results of the Traditional Birth Attendants is expected to make childbirth aid attention to safetyprocedures for both mother and baby.Key words: knowledge, attitude, labor action, traditional birth attendants